2023
DOI: 10.3389/fnmol.2023.1242925
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and pathologic transitions of RNP condensates in neurons: implications for amyotrophic lateral sclerosis, frontotemporal dementia and other neurodegenerative disorders

Aditi Naskar,
Asima Nayak,
Muthu Raj Salaikumaran
et al.

Abstract: Liquid–liquid phase separation results in the formation of dynamic biomolecular condensates, also known as membrane-less organelles, that allow for the assembly of functional compartments and higher order structures within cells. Multivalent, reversible interactions between RNA-binding proteins (RBPs), including FUS, TDP-43, and hnRNPA1, and/or RNA (e.g., RBP-RBP, RBP-RNA, RNA-RNA), result in the formation of ribonucleoprotein (RNP) condensates, which are critical for RNA processing, mRNA transport, stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 256 publications
0
3
0
Order By: Relevance
“…Among the hub genes derived from the up-regulated DEGs, no ALS-related literature was found for the EEF1A1 , RPLP0 , EEF2 , CCT2 , RPL12 and RPL15 genes. However, studies related to ALS were identified for the EIF4A1 [ 44 ], HNRNPR [ 45 ], HNRNPA1 [ 45 , 46 ] and PABPC1 genes [ 47 ]. In the case of hub genes obtained from the down-regulated DEGs, only the NDUFA4 gene was associated with ALS-related studies [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the hub genes derived from the up-regulated DEGs, no ALS-related literature was found for the EEF1A1 , RPLP0 , EEF2 , CCT2 , RPL12 and RPL15 genes. However, studies related to ALS were identified for the EIF4A1 [ 44 ], HNRNPR [ 45 ], HNRNPA1 [ 45 , 46 ] and PABPC1 genes [ 47 ]. In the case of hub genes obtained from the down-regulated DEGs, only the NDUFA4 gene was associated with ALS-related studies [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated expression of HNRNPR and HNRNPA1 together with a subset of human RNA-binding proteins that bind to the GGGGCC repeat RNA of the C9orf72 gene, one of the most common causes of ALS, reduces the level of GGGGCC repeat RNA, leading to the suppression of neurodegeneration. In addition, the involvement of HNRNPA1 in the different molecular pathways related to ALS neurodegeneration is increasingly being studied, as this protein is thought to play a key role in mRNA transcription, splicing, stability, transport and translation [ 46 , 63 ]. The PABPC1 gene has been associated with the UBQLN2 gene, one of the key genes linked to amyotrophic lateral sclerosis (ALS).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that PARP1 modulates liquid-liquid phase separation (LLPS) and a PARylation-mediated mechanism is likely involved in SERBP1’s pathological transition from condensate to aggregate. Several RBPs containing intrinsically disordered regions, like SERBP1, have been shown to display alterations in LLPS in neurodegenerative diseases (112, 113)…”
Section: Discussionmentioning
confidence: 99%
“…Protein condensation is a process by which proteins partition into a protein-rich phase, distinct from the more dilute bulk phase. The field of protein condensation has gained extraordinary popularity within the recent decade, with particular interest in biomolecular condensates (BMCs): cellular protein condensates with functional roles in spatiotemporal organization and regulation of biological processes [1][2][3], as well as involvement in diseases, such as neurodegeneration and cancer [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence 2 of 9 that these solid pathologic condensates originate from liquid condensates. Under stressful or pathological conditions, liquid condensates can undergo a liquid-to-solid phase transition, resulting in protein fibrillation [4,9].…”
Section: Introductionmentioning
confidence: 99%